Theoretical Studies of Stresses in a Layer of a Light-Concrete Mixture, Which is Compacted on the Shock-Vibration Machine - Nesterenko, Mykola; Nesterenko, Tetyana; Skliarenko, Taras (International Journal of Engineering and Technology, 2018)
The article presents the design of shock-and-vibration machine for the formation of lightweight concrete products. The results of theoretical studies of the working process of the shock-and-vibration machine with the definition of motion and stress laws in a layer of a concrete mixture compacted in the kinematic excitation of oscillations are given.In paper the dependences for determining the reduced mass and the equivalent coefficient of inelastic resistance of a concrete mixture with asymmetric kinematic excitation of oscillations during the vibration seal are given. The practical application of the obtained results is offered.Â Â